2019
DOI: 10.1128/mcb.00376-18
|View full text |Cite
|
Sign up to set email alerts
|

Common and Differential Transcriptional Actions of Nuclear Receptors Liver X Receptors α and β in Macrophages

Abstract: The liver X receptors α and β (LXRα and LXRβ) are oxysterol-activated transcription factors that coordinately regulate gene expression that is important for cholesterol and fatty acid metabolism. In addition to their roles in lipid metabolism, LXRs participate in the transcriptional regulation of macrophage activation and are considered potent regulators of inflammation. LXRs are highly similar, and despite notable exceptions, most of their reported functions are substantially overlapping. However, their indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 67 publications
4
30
0
Order By: Relevance
“…The repressive activity of RXR is based on direct DNA binding of the receptor together with silencing mediator of retinoic acid and thyroid hormone receptor (SMRT) and nuclear receptor corepressor (NCoR) corepressors and is largely insensitive to RXR ligand activation ( Figure 3B) (85). Recently, the synthetic agonist-and antagonist-insensitive (so-called pharmacologically non-responsive) fractions of LXRa and b cistromes were also identified in non-polarized murine immortalized BMDMs further confirming those opinions that the ligand insensitive fraction of lipid sensing nuclear receptor cistromes is general rather than cell type or nuclear receptorspecific phenomenon (86). It has been previously described that IL-4 can enhance the ligand-dependent activity of PPARg in human and murine alternatively polarized macrophages through three different mechanisms including EGR2 transcription factor-dependent activation of its expression, induction of endogenous ligand producing mechanisms, and direct protein-protein interaction with IL-4-activated STAT6 (87)(88)(89)(90).…”
Section: Lipid-sensing Nuclear Receptor-directed Ligand Insensitive Rsupporting
confidence: 67%
“…The repressive activity of RXR is based on direct DNA binding of the receptor together with silencing mediator of retinoic acid and thyroid hormone receptor (SMRT) and nuclear receptor corepressor (NCoR) corepressors and is largely insensitive to RXR ligand activation ( Figure 3B) (85). Recently, the synthetic agonist-and antagonist-insensitive (so-called pharmacologically non-responsive) fractions of LXRa and b cistromes were also identified in non-polarized murine immortalized BMDMs further confirming those opinions that the ligand insensitive fraction of lipid sensing nuclear receptor cistromes is general rather than cell type or nuclear receptorspecific phenomenon (86). It has been previously described that IL-4 can enhance the ligand-dependent activity of PPARg in human and murine alternatively polarized macrophages through three different mechanisms including EGR2 transcription factor-dependent activation of its expression, induction of endogenous ligand producing mechanisms, and direct protein-protein interaction with IL-4-activated STAT6 (87)(88)(89)(90).…”
Section: Lipid-sensing Nuclear Receptor-directed Ligand Insensitive Rsupporting
confidence: 67%
“…For example, RXRα (NR2B1) and RXRβ (NR2B2) were recently shown to have distinct functions in retinoic acid signaling and neuronal differentiation 48 . Both LXRα (NR1H2) and LXRβ (NR1H3) were each found selectively associated with sequence motifs of specific transcription factors demonstrating LXRα- or LXRβ-selective gene regulation in macrophages 49 . Since redundancy suggests dispensable or unnecessary, our data indicates that RORα is a requisite factor for T H 17 cell differentiation and the development of autoimmunity.…”
Section: Discussionmentioning
confidence: 96%
“…In support of the direct regulation of cholesterol biosynthesis by LXRs, Wang et al identified LXR binding sites in the promoters of human genes encoding several cholesterol biosynthetic enzymes and suggested that these sites function as negative regulatory elements (56). Published ChIP-Seq studies, however, have not demonstrated LXR binding in the vicinity of cholesterol biosynthetic genes in mouse BMDM (7,57). In BMDM, our data and previous studies indicate that cholesterol efflux is elevated in LXR knockout cells due to a loss of direct repression of ABC transporter expression mediated by LXR-corepressor complexes (45).…”
Section: Discussionmentioning
confidence: 99%